Utilizando o espaço escolar para trabalhar o ambiente construído em uma sequência didática - Paião, Maria Lucia (2021)
This work presents a proposal to work on environmental education in the Biology classes of high school with the objective of contributing to the formation of citizens able to decide and act on socio-environmental issues, and to sensitize students about the importance of conserving the environment in which they live, through a set of activities in the teaching of Biology. The research sought to work on the theme from the perspective of Ausubel's Theory of Meaningful Learning, with a problematic methodological approach in relation to Environmental Education in the contents of Biology, through the use of research and the investigative method in order to value the students' prior knowledge. and to arouse curiosity and a predisposition for learning. Among the objectives of the present investigation, is the elaboration of a teaching sequence, which was applied in a State School, the locus of the research, located on the outskirts of the city of Várzea Grande, in the State of Mato Grosso, on the outskirts of the city, with a class from 1st year of middle education. The methodology was based on qualitative research, considering the collaborating subjects and the researcher, which facilitated the analysis and understanding of the data obtained. When analyzing the data of the activities developed during the application of the teaching-learning sequences, you can notice at the end that the students had an advance in the understanding of the importance of taking care of the environment in which they live, giving meanings to their actions, such as changing understanding and posture that contributed in the learning and training of the critical subject with the reorganization of previous knowledge and relating them to new concepts.